The Cuban-American Transition: Demographic Changes Drive Ideological Changes* La transición Cubano-Americana: Cambios demográficos frente a cambios ideológicos - Guillermo J. Grenier (Universidad de La Habana, 2015)
Cuban-Americans are changing their attitudes about many of the key components of current US/ Cuba policy. The paper explores some of the social forces creating the patterns associated with the changing attitudes. Based on the data from the 2014 Cuba Poll, a descriptive analysis of relationships among key demographic variables uncovers compelling patterns associated with the ideological shift occurring in the population. Specifically, the patterns associated with ideology shifts and time of arrival of the migrant as well as his/her age and political party preference are explored. The paper makes clear that the new arrivals to Miami, as well as the younger Cubans, are significantly more interested in normalizing relations with the home country. Unfortunately, a large majority of the new arrivals (migrating since 1995), are not citizens and therefore not able to participate in the electoral processes that shape U.S. policy towards the island. Los cubano-americanos están cambiando sus actitudes acerca de muchos de los componentes clave de la política actual de Estados Unidos hacia Cuba. El artículo explora algunas de las fuerzas sociales que crean los patrones asociados a esas actitudes cambiantes. En base a los datos del 2014 Cuba Poll, un análisis descriptivo de las relaciones entre las variables demográficas clave, el texto descubre patrones de peso asociados con el cambio ideológico que ocurre en la población. En concreto, patrones asociados con los cambios y el tiempo de llegada de los migrantes, así como su edad y preferencia de partido político o de ideología. El documento deja claro que las personas recién llegadas a Miami, así como los jóvenes cubanos, están significativamente más interesados en la normalización de las relaciones con su país de origen. Por desgracia, la gran mayoría de los recién llegados (desde 1995), no son ciudadanos estadounidenses y, por tanto, no pueden participar en los procesos electorales que dan fforma a la política de Estados Unidos hacia la isla.